Iron ion-coordinated carrier-free supramolecular co-nanoassemblies of dual DNA topoisomerase-targeting inhibitors for tumor suppression. (May 2022) - Guan, Jianhuan; Tan, Xiao; Jiao, Jian; Lai, Shuang; Zhang, Haotian; Kan, Qiming; He, Zhonggui; Sun, Mengchi; Sun, Jin
Abstract: Overexpressed DNA topoisomerase II alpha (TOP-2A) is closely related to the invasion and metastasis of malignant breast tumors. Mitoxantrone (MTX) has been identified as a TOP-2A inhibitor with significant inhibitory activity against breast tumors. The tumor-homing ability of MTX has been further enhanced by using nanodrug delivery systems (nano-DDSs), reducing off-target side effects. However, conventional MTX nano-DDSs are still limited by low drug-loading capacity and material carrier-related toxicity. In this study, we developed metal iron-coordinated carrier-free supramolecular co-nanoassemblies of dual DNA topoisomerase-targeting inhibitors with high drug loading for superimposed DNA damage-augmented tumor regression. By introducing iron ions (Ⅲ) and another TOP-2A inhibitor quercetin (QU) onto the building blocks, Fe 3+ -mediated QU-MTX co-nanoassemblies are fabricated (QU-MTX-Fe) via intermolecular coordination interactions. The PEGylated co-nanoassemblies (P-QU-MTX-Fe) exhibit distinct advantages over QU/MTX solution (Sol) alone or MTX-QU mixture Sol in terms of therapeutic efficacy and systemic toxicity. Meanwhile, P-QU-MTX-Fe could efficiently suppress primary and distal breast tumor relapse by activating the CD 8 + -mediated antitumor immune response. Overall, such iron-coordinated nanomedicines provide insights into the rational design of drug-likeness compounds with undesirable therapeutic performance for cancer therapy. Statement of significance: Aimed at the key target TOP-2A in the malignant breast tumor, the metal coordination-mediated supramolecular co-assemble strategy of one-target dual inhibitors was firstly proposed for superimposed DNA damage for cancer therapy. Multiple interactions involving π-π stacking interactions, hydrogen bonds and coordination forces maintained the stability of co-nanoassemblies. Meanwhile, this co-nanoassemblies not only had potentials to increase therapeutic efficacy and decrease systemic toxicity, but also activated the CD 8 + -mediated antitumor immune response against distal breast tumor relapse. Such a facile and safe nanoplatform is expected to provide an important prospective for promoting the clinical transformation of drug-likeness compounds in the suppression of difficult-to-treat breast tumor. Graphical abstract: Image, graphical abstract